Association of homocysteine and polymorphism of methylenetetrahydrofolate reductase with early-onset post stroke depression - Zhang, Jingyuan; Zeng, Chang; Huang, Xia; Liao, Qiao; Chen, Hengshu; Liu, Fan; Sun, Dongren; Luo, Shihang; Xiao, Yeqing; Xu, Weiye; Zeng, Danfeng; Song, Mingyu; et al. (Frontiers in Nutrition, 2022)
Background: Homocysteine (Hcy) has been indicated to be involved in pathophysiology of post stroke depression (PSD). There is a lack of research to study the relationship between Hcy metabolism genes and PSD. Our study aims to investigate the relationship among Hcy metabolism genes, Hcy, and early-onset PSD. Method: We recruited 212 patients with stroke and collected their peripheral blood sample, clinical data, and laboratory test on admission. 12 single nucleotide polymorphisms (SNPs) in MTHFR, MTRR, and MTR genes were genotyped by high-resolution melt analysis. PSD was diagnosed by DSM-V at 2 weeks after stroke. Binary logistic regression and haplotype analysis were used to examine the association between Hcy metabolism genes and PSD. Mediation analysis was performed to clarify whether the SNPs exerted their effect on PSD by affecting the Hcy level. Result: 81 patients were diagnosed with PSD, and the incidence rate was 38.2%. Hcy level in PSD group was significantly higher than it in non-PSD group (p=0.019). MTHFR rs1801133 AA genotype an A allele were associated with an elevated risk of PSD after adjustment for some confounding factors (OR=4.021, 95%CI: 1.459~11.080, p=0.007 for AA genotype; OR=1.808, 95%CI: 1.172~2.788, p=0.007 for A allele). Furthermore, the effect of MTHFR rs1801133 AA genotype on PSD was mediated by Hcy (OR=1.569, 95%CI: 0.013~3.350, p<0.05). Conclusion: MTHFR rs1801133 and Hcy were associated with PSD, and MTHFR rs1801133 may exert an effect on PSD via mediating Hcy level. This offers a new perspective for treating PSD and understanding the mechanism of PSD.